ECONOMIC AND MATHEMATICAL MODEL FOR FORECASTING DIRECTIONS OF DEVELOPMENT OF HUNTING ENTERPRISES - Hul Ivan Grygorovych; Zavydivska Olga Igorivna; Moroz Volodymyr Pavlovych; Mandryk Vasyl Olegovych (Scientific Journal of Pedagogy and Economics, 2020)
The article summarizes arguments and counterarguments within the scientific discussion on the development of the hunting enterprises. The aim of the article is to construct an economic and mathematical model for determining the number of wild hunting animals, in which the production and economic activity of the enterprises of the hunting economy will be able to operate on the basis of self-sustainability and self-financing. The actuality of solving of this scientific problem is in the necessity of reformation of the hunting economy in Ukraine, which provides formation of the national conception of its organization and development, which would base on the effective economic, ecological and social instruments; and which, at the same time, would take into account national management traditions. In order to construct an economic and mathematical model for predicting the directions of development of the hunting enterprises, the research was conducted in the following logical sequence: analyzed by what components are formed the total costs and total revenues from hunting economy; the boundary between the unprofitable and break-even level of hunting activity; according to the objective function, the theoretical principles of the economic and mathematical model were formulated, which allow to define the break-even quantity of hunting animals; four directions of development of the hunting enterprises are considered. The methodical basis of the study were the methods of analysis, synthesis, economic and mathematical modeling, statistical method; the period of research – 2016-2017 years. The hunting facility of the Lviv region (Ukraine) was chosen as the object of the research as it gave us the opportunity to carry out additional calculations taking into account more optimistic directions of hunting economy development. The research empirically confirms and theoretically proves that the hunting economy can function on the principles of self-sustainability and self-financing without going beyond the established and legally established norms.